Harm reduction in cartilage tissue engineering experimentation: a comparative review between Islamic and conventional ethics / Muhammad Aa’zamuddin Ahmad Radzi … [et al.] - Ahmad Radzi, Muhammad Aa’zamuddin (2015)
Articular cartilage acts as a load-bearer in human joints. It is prone to injuries or damages by various factors which may lead to irreversible osteoarthritic condition if left untreated. Cartilage Tissue Engineering (TE) is a part of regenerative medicine domains which aims to repair, regenerate and restore cartilage biological functions. Despite this great discovery, harm and therapeutic uncertainties spark the ethical concerns surround the technology. This review paper identifies the potential harms in cartilage TE and suggest ways to overcome those issues before the technique can be applied to the patients. The paper presents a discourse from Islamic and conventional ethical viewpoints. The diverse outlooks include their definition of ethics and their sources of references. A thorough examination of the processes in cartilage TE experimentation; serves to give the audience a clear view of the possible or underlying ethical issues, the details of which are explained in this paper. Among the issues to be discussed are; (1) cell harvesting from donor, (2) materials use and safety concerns of implanted constructs, and (3) animal utilization in proof of concept study. Islamic ethics and conventional ethical theories seem to be in agreement on the general principles of harm reduction in cartilage TE. However, there are differences between the approaches of these two ethical systems on issues related to the cartilage TE principles. To be able to harmonise the differing stances between Islamic and conventional bioethics can help bridge those differences within the socio-religious context. Furthermore, it should benefit the Muslim practitioners in terms of the presence of a discourse that could reduce the Islamic religious concerns towards the technique. It is hoped that all the identified socio-religious ethical challenges in cartilage TE can be addressed before it reaches the clinical application. Indeed, this technology can be applied in a minimally invasive manner.